Comparative dielectric study of bent-core liquid crystal doped 5CB - Canli, N. Yilmaz; Erdogan, M.; Kavak, P. (TAYLOR & FRANCIS LTD, 2021)
Bent-core liquid crystal (LC) is used to dope the (4-cyano-4 '-pentylbiphenyl) liquid crystal (5CB). The polarizing microscopy results show that 5CB and LC exhibit Nematic (N) and Banana-Shaped (B-1) mesophases, respectively. In this paper, we use dielectric spectroscopy to determine the dielectric properties of the 1% LC doped with 5CB liquid crystal. The dielectric parameters of these materials have been determined by different applied voltage. In this respect, dielectric properties of 5CB + 1% LC have been compared with 5CB. The dielectrical anisotropy of 5CB and 5CB + 1% LC liquid crystal composite changes from the positive dielectric anisotropy to negative with the frequency of the applied voltage. The critical frequency f(c) values of dielectrical anisotropy for 5CB and 5CB + 1% LC composite were found to be 688 and 534 kHz, respectively. The real (epsilon ') and imaginary components (epsilon '') of dielectric constant have been calculated by capacitance method. It has been also determined that adding LC to 5CB decreases the voltage dependent dielectric strength and increases threshold voltages.
Keywords: Liquid crystal; dielectric constants; dielectric strength; dielectric anisotropy; MEMORY; PHASES; Materials Science; Physics